Novel biotinylated bile acid amphiphiles: Micellar aggregates formation and interaction with hepatocytes - Rizzi, L.; Braschi, M.; Colombo, M.; Vaiana, N.; Tibolla, G.; Norata, Giuseppe; Catapano, A.; Romeo, S.; Prosperi, D. (Royal Society of Chemistry, 2011)
Amphiphilic bile acids linked through an oligoethylene glycol to a biotin moiety were synthesized and shown to create micellar structures in aqueous environment, interact with avidin and be efficiently incorporated into hepatocyte cells, suggesting their potential as a drug delivery system against liver diseases. © 2011 The Royal Society of Chemistry.